Predicting mortality from septic shock among pediatric population in emergency room - Jayapal, Karthick (International Journal of Contemporary Pediatrics, 2020)
Background: Sepsis is defined as systemic inflammatory response syndrome in the presence of a suspected or known invasive infection and septic shock is defined as sepsis and cardiovascular organ dysfunction which persists even after initial fluid resuscitation. It is important to identify the risk of progression of sepsis to septic shock and death in the pediatric age group in order to prevent mortality. Methods: This cohort study was carried out among 142 children aged between one month and 18 years who were diagnosed with sepsis in the emergency room (ER). All the hemodynamic and laboratory parameters were evaluated. The participants were followed up for a period till recovery/death. Particulars related to the management of the cases in terms of fluid resuscitation, inotropes and antibiotics were also documented. Results: Majority of the participants were aged between 1-10 years and were males. There was a statistically significant difference in the temperature, total leukocyte count and other biochemical parameters between survivors and non survivors (p<0.05). Initiation of antibiotics within one hour was significantly higher among the survivors compared to the non survivors (p<0.05). Conclusion: There is a need for immediate and early detection of abnormalities in the clinical and laboratory parameters in order to prevent mortality due to septic shock in the pediatric emergency room.